Glyphosate affects methylation in the promoter regions of selected tumor suppressors as well as expression of major cell cycle and apoptosis drivers in PBMCs (in vitro study). (March 2020) - Woźniak, Ewelina; Reszka, Edyta; Jabłońska, Ewa; Balcerczyk, Aneta; Broncel, Marlena; Bukowska, Bożena
Abstract: We have determined the effect of glyphosate on selected epigenetic parameters and major cell cycle drivers in human peripheral blood mononuclear cells (PBMCs). The cells were incubated with glyphosate at 0.5, 10 and 100 μM. The analysis included: global DNA methylation, methylation in the promoter regions of tumor suppressor genes ( P16, P21, TP53 ) and proto-oncogenes ( BCL2, CCND1 ) by the Real-Time PCR and the expression profile of the indicated genes by Real-Time PCR. The obtained results have revealed significant reduction of global DNA methylation level in PBMCs exposed to glyphosate. Tested compound changed methylation pattern of the P21 and TP53 suppressor gene promoters, but in case of other analyzed genes: P16, BCL2 and CCND1 we did not identify any statistically significant changes. Gene profiling showed that glyphosate changed the expression of genes involved in the regulation of cell cycle and apoptosis. Glyphosate decreased expression of P16 and TP53 as well as an increase in the expression of BCl2, CCND1 and P21 . Summing up, our results have shown a potential disturbance in methylation processes and gene expression in human PBMCs exposed to glyphosate, but the observed changes do not prejudge about the final metabolic effects, which are depended on many other factors. Graphical abstract: Unlabelled Image Highlights: Glyphosate significant reduction of global DNA methylation level in human PBMCs. Glyphosate changes methylation pattern of the P21 and TP53 gene promoters. Glyphosate changes the expression genes involved in regulation of cell cycle ( CCND1, P16, P21 and TP53 ) and apoptosis ( BCL2 ).